Electrospun of PVP Nanofiber Doped with Au Nanoparticles for UV-Detector - Abdul Hamid, Marwan S.; M. Ibrahim, Isam (Iraqi Journal of Physics, 2025)
Pure polyvinylpyrrolidone (PVP) nanofibers were doped with different concentrations of gold nanoparticles (Au NPs) using the electrospinning technique. The characteristics of both nanofibers were investigated using X-ray diffraction (XRD), field emission scanning electron microscope (FE-SEM), and UV-visible properties. The structure of PVP-Au was amorphous, as revealed by XRD. A DC voltage of 20 kV was applied to Au-PVP nanofiber beads on glass substrates and silicon wafers of n-Si type, oriented (111), at room temperature. The effect of doping on some physical properties (structural, optical, electrical, and sensitivity) of the polymer material was studied. The physical properties of the material composite film fibres were studied as the concentration of Au rises. The optical energy gap for three Au-PVP samples ranged between 3.60 and 3.70 eV. The responsivity for Au-PVP nanofibers was obtained for the UV detector, where the optimum detector sensitivity was at the wavelength of 360 nm. The sensitivity values obtained were 2.4, 17.5, and 24.45 for doping ratios 0.1:9.9, 0.5:9.5, and 1:9, respectively, with the values of the rise time ranging from 2.40 to 24.45s and fall time 10.2- 22.3s for Au concentrations.